1997
DOI: 10.1139/g97-089
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal RNA genes specific to the B chromosomes in Brachycome dichromosomatica are not transcribed in leaf tissue

Abstract: Ribosomal RNA genes are present near the end of the short arm and, to a lesser extent, near the centromere of the B chromosomes of some populations of Brachycome dichromosomatica. The internal transcribed spacer (ITS2) was amplified by PCR from total leaf DNA using primers within the conserved regions encoding the 5.8S and 25S stable rRNA species. Comparison of PCR amplified ITS2 sequences from several individual plants without B chromosomes with corresponding sequences derived from microdissected B chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Isolation of RNA and DNA: Total cellular RNA and DNA of C. capillaris were prepared from young leaves and flower buds as previously described (Donald et al 1997). DNA of herbarium specimens of Crepis species was isolated by using a DNeasy plant kit (QIAGEN, Chatsworth, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of RNA and DNA: Total cellular RNA and DNA of C. capillaris were prepared from young leaves and flower buds as previously described (Donald et al 1997). DNA of herbarium specimens of Crepis species was isolated by using a DNeasy plant kit (QIAGEN, Chatsworth, CA).…”
Section: Methodsmentioning
confidence: 99%
“…These loci do not silver stain and Donald et al (1997) were unable to detect a transcription product using PCR, of reverse-transcribed total RNA from leaf tissue of plants containing B chromosomes, with primers specific to the internal transcribed spacer 2 (ITS2) of the B chromosome rRNA gene.…”
mentioning
confidence: 99%
“…Presence of rDNA on B-chromosomes reported in several plant species (Flavell and Rimpau 1975, Maluszynska and Schweizer 1989, Donald et al 1995, 1997, Friebe et al 1995, Jones 1995, Dhar et al 2002, Xie et al, 2014 and rDNA of B-chromosome was inactive in most species excepting for Allium cernuum (Friebe et al 1995). The mechanism of suppression of rDNA in B-chromosomes was not revealed.…”
Section: Resultsmentioning
confidence: 97%
“…The ITS2 sequence has been examined in previous studies for three B chromosomes containing 45S rDNA. Two of them differed in only 2 bp (0.9%) from the ITS2 sequence on their host genome (Donald et al 1997;Marschner et al 2007), whereas in Crepis capillaries two ITS2 sequences on the B chromosome were found that differed in 11 bp (4.8%) and 14 bp (6.1%) from that on the A chromosomes (Leach et al 2006). Here we show that the PSR chromosome in T. kaykai has at least four ITS2 sequences that are not only very different from the host ITS2, but also from any ITS2 sequence.…”
Section: Discussionmentioning
confidence: 92%
“…Extensive studies on rDNA in B chromosomes have demonstrated that a large number of B chromosomes contain 45S rDNA cistrons (Maluszynska & Schweizer 1989;Ló pez-Leó n et al 1994, 1999Jones 1995;Donald et al 1997;Cabrero et al 1999;Stitou et There are a number of possible explanations for this phenomenon: (i) 45S rDNA is more prone to chromosome breakage, possibly because its location is usually at the end of a chromosome; (ii) 45S rDNA may be susceptible to meiotic isolation, because it has little or no crossing-overs, disjoins later in anaphase I and has a different timing of expression than the rest of the genome; (iii) B chromosomes without 45S rDNA may arise, but then easily obtain hypertransposable rDNA sequences (Schubert & Wobus 1985;Beukeboom 1994;Jones 1995). The ITS2 sequence has been examined in previous studies for three B chromosomes containing 45S rDNA.…”
Section: Discussionmentioning
confidence: 99%